Análisis del uso de los celulares por parte de los estudiantes de la carrera de Comunicación Social como herramienta educativa en su proceso de aprendizaje - Mullo Sisa, Cristhian Joselito (2020)
The main purpose of the present investigation is to determine the use of mobile devices or smart cell phones in the learning process in the students of the Social Communication Career of the Technical University of Babahoyo during the year 2019 of the city of Babahoyo province of The rivers. Through the literature and field research, the possession of smartphones by students who used them in classrooms as a pedagogical instrument was identified. The study showed that mobile smart cell phones are a very useful tool for students when conducting their research; Therefore, the respective conclusions and recommendations were made. Based on the results of the study, it is concluded that the use of mobile smart cell phones enhances the interaction of the students of the Social Communication Career inside and outside the classroom stimulating research, communication, critical and reflective thinking.